2015
DOI: 10.3747/pdi.2014.00188
|View full text |Cite
|
Sign up to set email alerts
|

Transition of Mesothelial Cell to Fibroblast in Peritoneal Dialysis: EMT, Stem Cell or Bystander?

Abstract: Long-term peritoneal dialysis (PD) can lead to fibrotic changes in the peritoneum, characterized by loss of mesothelial cells (MCs) and thickening of the submesothelial area with an accumulation of collagen and myofibroblasts. The origin of myofibroblasts is a central question in peritoneal fibrosis that remains unanswered at present. Numerous clinical and experimental studies have suggested that MCs, through epithelial-mesenchymal transition (EMT), contribute to the pool of peritoneal myofibroblasts. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 153 publications
(214 reference statements)
3
64
0
1
Order By: Relevance
“…EMT is a highly regulated process that has a vital role in embryonic development, tumor formation and fibrosis in some chronic inflammatory diseases [3,4]. Peritoneal mesothelial cell EMT is one of the key factors responsible for gradual decreases in peritoneal functions in peritoneal dialysis patients [3,4]. TGF-β1 is an important fibrosis-promoting factor in several tissues and organs, including peritoneal tissue; its role is to phosphorylate the signaling protein smad2 /3 [17].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…EMT is a highly regulated process that has a vital role in embryonic development, tumor formation and fibrosis in some chronic inflammatory diseases [3,4]. Peritoneal mesothelial cell EMT is one of the key factors responsible for gradual decreases in peritoneal functions in peritoneal dialysis patients [3,4]. TGF-β1 is an important fibrosis-promoting factor in several tissues and organs, including peritoneal tissue; its role is to phosphorylate the signaling protein smad2 /3 [17].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have found that the long-term stimulation by nonbiocompatible peritoneal dialysis solution can lead to the EMT of peritoneal mesothelial cells [2,3,16]. EMT is a highly regulated process that has a vital role in embryonic development, tumor formation and fibrosis in some chronic inflammatory diseases [3,4]. Peritoneal mesothelial cell EMT is one of the key factors responsible for gradual decreases in peritoneal functions in peritoneal dialysis patients [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations